The Form of Arguments Using Argument Reconstruction in Online Media Articles - Parai, Hestiyani; Boeriswati, Endry; Anwar, Miftahulkhaira (Bina Nusantara University, 2018)
This research aimed to identify the form of arguments in online media articles using argument reconstruction. The data were argumentative texts written in online media article in 2017 in www.hipwee.com, malesbanget.com, and www.idntimes.com. The data studied were 44 paragraphs consisting of 150 sentences. The approach used was qualitative approach by using content analysis method. This research used the triangulation technique (combination). The simultaneous data collection was coupled with data credibility tests with various data collection techniques and sources. Meanwhile, means of documentation and content analysis techniques were done to collect the data. The results indicate that the often used reasonings in online media articles are the generalization in 11 paragraphs and categorical syllogism in 28 paragraphs. The results of this research can be used to find out and develop ways of writing online media articles for writers and readers of online media articles.